Preliminary report on equisetalean plants from Lidgetton, Natal - (:unkn) unknown (Bernard Price Institute for Palaeontological Research, 1976)
Fossils of Equisetum-like plants from a site near Lidgetton, Natal, South Africa (29"26'S, 30"07' E) are described. These comprise rhizomes bearing roots, stems of varying width showing external and some internal structure (especially nodal markings and vasculature), and ultimate branchlets bearing leaf whorls. No reproductive organs were found. A tentative decision is reached that they are parts of plants of a single genus, perhaps even a single species, and that relationship is closest to Equisetites Sternberg.
Main article
Keywords: Equistalean; plants; Natal